Digital Marketing Strategies and Competitive Advantage among Tourism-Based Microenterprises - Elinda Novita Dewi; Alfa Rohmatin; Ayu Ambarwati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The increasing digitalization of tourism markets has intensified competition among tourism-based microenterprises, requiring strategic use of digital marketing to achieve and sustain competitive advantage. Despite widespread adoption of digital tools, empirical evidence explaining how digital marketing strategies translate into competitive outcomes in microenterprise contexts remains limited. This study aims to examine the relationship between digital marketing strategies and competitive advantage among tourism-based microenterprises through an empirical, explanatory research design. Data were collected from tourism microenterprises using a structured questionnaire and analyzed using multivariate statistical techniques, including reliability testing and structural modeling. The results indicate that digital marketing strategies significantly influence competitive advantage, particularly through content engagement, platform integration, and online customer interaction, while basic digital presence alone yields weaker performance effects. The findings further reveal that leadership orientation, collaborative ecosystems, and sustainability-oriented practices strengthen the effectiveness of digital marketing strategies in enhancing differentiation, market reach, and customer retention. The discussion highlights that digital marketing functions as a dynamic strategic capability rather than a mere technological adoption, with long-term competitive advantage emerging from continuous learning, capability development, and alignment with local tourism values. This study contributes to tourism and small business literature by clarifying the mechanisms linking digital marketing strategies to competitive advantage and offers practical implications for microentrepreneurs and policymakers in digitally contested tourism environments.